PERANCANGAN KOMPOR SEKAM PADI PADA INDUSTRI PEMBUATAN TAHU XYZ MENGGUNAKAN METODE KANSEI ENGINEERING - Dwi Puspitasari; Sugiharto P; Anizar M.kes (Departemen Teknik Industri Universitas Sumatera Utara, 2014)
Along with economic growth and increasing population led to the development of industry and energy consumption in the world, Among the various types of energy, fuel wood is thought to be the oldest energy sources used by humans . The problem is the use of firewood production is insufficient for the needs of sustainable consumption. In XYZ tofu makin industry that still use wood as a fuel acknowledges the high price of fuel used in the production process, for each week, it takes about 350 kg of firewood or equivalent for Rp. 450.000 for each week or about 58 kg at a price of Rp 75.000 for a day . Recommended alternative is the use of the use of rice husk as an alternative energy source material on the process of cooking tofu porridge. To convert waste rice husks into energy alternatives , then the required burner in accordance with the husk fuel. Husk stove is designed with the approach of Kansei Engineering is a method that brings together technology Kansei (feeling and emotion) with engineering disciplines. Through the results of questionnaires obtained 9 kansei words into positive husk stove design parameters. According to the results of the calculation of the need to heat the slurry chaff needs to know by one time cooking takes 49 kg of rice husk, so for one day of production required chaff as much as 197,2 kg or equivalent to Rp 29.800